Sampling with probability proportional to aggregate size using nonparametric bootstrap ion estimating total production area of top cereals and root crops across Philippine regions - Poblador, Maria Sofia Criselda A.; Gauran, Iris Ivy M. (2012)
Cereal and root crop production are of primary interest to the country's agricultural industry. The need to obtain reliable estimates of total area of production is therefore crucial. This paper examines the Sampling with Probability Proportional to Aggregate Size (PPAS) in terms of unbiasedness and precision of estimates as compared to two known sampling designs, Simple Random Sampling without Replacement (SRSWOR) and Sampling with Probability Proportional to Size Without Replacement (PPSWOR).

Crop area, is used as auxiliary information. Estimates of total production area are obtained at 1%, 5% and 10% sampling rates. To be able to evaluate precision of PPAS estimates, nonparametric bootstrap variance estimation is performed.

PPAS estimates are generally better than the two other sampling designs when it comes to precision but almost at par when it comes to unbiasedness.
Keywords: Random sampling; Non-parametric statistics; Bootstrap estimation; Cereal products; Root crops